PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE INKUIRI TERHADAP HASIL BELAJAR SISWA KELAS IV SD - Santa Nadia Br Purba; Reflina Sinaga; Juliana; Patri Janson Silaban (Jurnal PAJAR (Pendidikan dan Pengajaran), 2021)
This study aimed to determine the effect of using the Cooperative Type Inquiry learning model on students' learning outcomes for the theme "Indahnya Keberagaman di Negeriku" at grade IV SDN 060938 Medan Johor in the Academic Year 2020/2021. The population of this study was all grade IV students, and 30 students were selected as samples using purposive sampling. This research employed a descriptive-analytical method. The results showed that students' learning outcomes after the implementation of the Cooperative Type Inquiry model were categorized as excellent, with an average score of 82.96. The normality test indicated that the learning outcomes were normally distributed (Lcount > Ltable, 0.178 > 0.05), while the correlation coefficient was 0.621 (rcount ≥ rtable, 0.621 > 0.361). The t-test result was 4.195 > 1.697, indicating that Ha was accepted, meaning there was a positive and significant effect of the Cooperative Type Inquiry learning model on students' learning outcomes.